Pengaruh Komunikasi Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan PT Maxin Paint Medan - Michael Halim; Juli Meliza (Cattleya Darmaya Fortuna, 2022)
This study aims to determine and analyze the effect of communication and physical work enviroment on employee performance PT. Maxin Paint Medan. The paint company's employees had communication and physical work enviroment problems. The problems that occured were dealing with the number of errors caused by miscommunication and production decrease. This study used a quantitative approach with 86 respondents as sample. The results showed that Communication and Physical Work Enviroment partially had a positive and significant effect on the performance of employees of PT Maxin Paint Medan.